Dose–response effects of vitamin D supplementation on vitamin D status, glycosylated hemoglobin and total cholesterol in patients with diabetes mellitus: a systematic review and meta-analysis - Cao, Lu; Zhou, Nan; Zhang, Dan; Zhang, Peng; Zhao, Ying (Frontiers in Nutrition, 2025)
The impact of vitamin D levels on glycemic control and lipid metabolism in diabetic patients has received widespread attention. However, currently, there was no unified standard for vitamin D supplementation dosages, with significant variations among guideline recommendations. For instance, the 2022 ESPEN Guidelines recommended a daily supplementation of 1,500–5,000 International Units (IU) for patients at risk of vitamin D deficiency or who repeatedly experience vitamin D deficiency; however, guidelines from Italy suggested a daily supplement dose of 800–1,000 IU for patients with vitamin D deficiency. In this study, we searched the PubMed, Web of Science, Embase, Cochrane Library, CBM, CNKI, and Wanfang databases from their inception to 31 May 2024 for literature. The effects of different supplementation levels on vitamin D levels, glycosylated hemoglobin (HbA1c) levels and total cholesterol (TC) levels were analyzed using random-effects and fixed-effects models, respectively, and we applied the Modified Jadad Scale and the Newcastle-Ottawa Scale (NOS) score to evaluate the quality of the RCT studies and retrospective analyses, respectively. We included a total of seven papers involving 468 patients with a follow-up period of 3 to 6 months. The results of the study showed that vitamin D levels were significantly higher in the high-dose group than in the low-dose group at both 3 and 6 months of treatment [mean difference (MD) = −12.48, 95% confidence interval (CI): −15.25 to −9.72 and MD = −28.22, 95% CI (−40.92, −15.72), both p < 0.05], and the effect of prolonged treatment was more significant. HbA1c levels were significantly lower in the high-dose group than in the low-dose group [MD = 0.41, 95% CI (0.14, 0.67), p = 0.003], and TC levels were not significantly different between the two groups [MD = 1.84, 95% CI (−8.07, 0.67), p = 0.72]. Therefore, in patients with diabetes mellitus complicated by vitamin D deficiency, higher-dose supplementation (>4,000 IU/day) might have had potential advantages in increasing vitamin D levels and improving glycemic control. However, further studies were still needed to clarify the long-term safety and risk–benefit ratio of higher-dose supplementation.